Study on the Mitigative Effect of Controlled Permeable Formwork (CPF) Liner on Early-Age Shrinkage of Box-Girder Concrete. (10th September 2019) - Ye, Jianxiong; Yu, Linwen; Chen, Yong
Abstract : Because of its high binder content and severe construction environment, early-age cracking is one of the most important threats to concrete used in continuous box-girder bridge structures. In this study, controlled permeable formwork (CPF) liner was used to mitigate the early-age shrinkage and reduce the early-age cracking risk of box-girder concrete. Early-age shrinkage was measured by a noncontact method and started at 30 min after adding mix water until 7 d. Internal relative moisture content and pore distribution tests were also carried out to reveal the working mechanism of CPF liner. The results show that covering the concrete surface with CPF liner decreased early-age shrinkage significantly. Under the temperature of 20°C and the relative humidity of 60%, two-surface-covering and three-surface-covering CPF liner on concrete decreased the shrinkage by 44% and 48%, respectively, at 7 d compared with concrete without CPF liner covered on it. The main reason is that CPF liner enhanced the internal relative moisture content and resulted in better performance of the surface concrete.